MEMBANGUN HUBUNGAN HARMONIS DALAM PELAKSANAAN FUNGSI PENGAWASAN HAKIM OLEH MAHKAMAH AGUNG DAN KOMISI YUDISIAL DALAM RANGKA MENEGAKKAN KEHORMATAN, KELUHURAN DAN MARTABAT HAKIM - Rumadan, Ismail (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2016)
The existence of Judicial Commission, a state institution function as an external control for ethic code and judges code of conduct, often collide with an internal control function which carried out by Supreme Court. Both institutions were overlapping so that many energy been wasted for handling the problem raised. Both parties have to realize each position and area. They have to coordinate to do controlling function harmoniously in judicial technical context for honor, dignity and judges behavior.Keywords : Supreme Court, Judicial Commission, control function